EGFR Polymorphism as a Predictor of Clinical Outcome in Advanced Lung Cancer Patients Treated with EGFR-TKI - Jung, Minkyu (Yonsei University College of Medicine, 2012)
PURPOSE: Mutations in the epidermal growth factor receptor (EGFR) have been confirmed as predictors of the efficacy of treatment with EGFR-tyrosine kinase inhibitors (TKIs). We investigated whether polymorphisms of the EGFR gene were associated with clinical outcomes in non-small cell lung cancer (NSCLC) patients treated with EGFR-TKI. MATERIALS AND METHODS: A polymorphic dinucleotide repeat in intron 1 [CA simple sequence repeat in intron 1(CA-SSR1)] in intron 1 and single nucleotide polymorphisms (SNP-216) in the promoter region of the EGFR gene were evaluated in 71 NSCLC patients by restriction fragment length polymorphism and DNA sequencing. The relationship between genetic polymorphisms and clinical outcomes of treatment with EGFR-TKIs was evaluated. RESULTS: SNP-216G/T polymorphisms were associated with the efficacy of EGFR-TKI. The response rate for the SNP-216G/T tended to be higher than that for G/G (62.5% vs. 27.4%, p=0.057). The SNP-216G/T genotype was also associated with longer progression-free survival compared with the GG genotype (16.7 months vs. 5.1 months, p=0.005). However, the length of CA-SSR1 was not associated with the efficacy of EGFR-TKI. CONCLUSION: SNP-216G/T polymorphism was a potential predictor of clinical outcomes in NSCLC patients treated with EGFR-TKI.